2017
DOI: 10.1093/hropen/hox010
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight and PCOS: systematic review and meta-analysis

Abstract: STUDY QUESTION Are intrauterine conditions, reflected in birthweight, associated with the development of polycystic ovary syndrome (PCOS)? SUMMARY ANSWER Our study indicates that a low birthweight as a summary measure of intrauterine environment may be associated with PCOS when diagnosed according to the Rotterdam criteria. WHAT IS ALREADY KNOWN The etiology of PCOS is still largely unknown. Besides subfertility, women diagnosed with PCOS hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Despite speculations of such an association, findings from previous studies are inconsistent. A recent meta-analysis of 14 studies found that a low birthweight might increase the risk of PCOS [9], but a subsequent, largescale, registry-based study from Sweden did not find an association [24]. Thus, based on the current evidence, the role of birthweight in the etiology of PCOS is still uncertain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite speculations of such an association, findings from previous studies are inconsistent. A recent meta-analysis of 14 studies found that a low birthweight might increase the risk of PCOS [9], but a subsequent, largescale, registry-based study from Sweden did not find an association [24]. Thus, based on the current evidence, the role of birthweight in the etiology of PCOS is still uncertain.…”
Section: Discussionmentioning
confidence: 97%
“…As clinical manifestations of PCOS often emerge during the teenage years, the preceding years from birth and throughout childhood may be a critical period for this condition to develop. Birthweight, as an indicator of the intrauterine environment, may be inversely associated with PCOS risk but there is uncertainty about this, as the association is not significant in largescale studies, suggesting a publication bias [9]. Six studies have investigated links between body size in childhood and a subsequent risk of developing PCOS, and generally found positive associations [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, Kobayashi et al (50) suggested that the literature varied on this subject. In another example, PCOS was found in some, but not all, studies to be associated with increased PTB and LBW (51,52).…”
Section: Infertility Diagnosesmentioning
confidence: 96%
“…Based on the well-known developmental origins of health and disease, an inverse association between birth weight and T2D risk seems highly likely. Indeed, low birth weight has been associated with PCOS diagnosis later in life, with a birth weight < 2.5 kg conferring a 76% higher likelihood of developing PCOS[ 84 ]. In a similar manner, age of menarche has been related to dysglycemia in PCOS.…”
Section: Risk Factors For the Development Of T2d In Pcosmentioning
confidence: 99%